Fabrications, Applications and Challenges of Solid-state Nanopores: A Mini Review - Zifan Tang; Daihua Zhang; Weiwei Cui; Hao Zhang; Wei Pang; Xuexin Duan (Nanomaterials and Nanotechnology)
Nanopore sensors are expected to be one of the most promising next generation sequencing technologies, with label-free, amplification-free and high-throughput fea‐ tures, as well as rapid detections and low cost. Solid-state nanopores have been widely explored due to their diverse fabrication methods and CMOS compatibility. Here, we highlight the fabrication methods of solid-state nanopores, including the direct opening and the tuning methods. In addition, molecular translocation developments, DNA sequencing and protein detections are summarized. Finally, the latest progress relating to solid-state nanopores is discussed, which helps to offer a comprehensive under‐ standing of the current situation for solid-state nanopore sensors.